PENGARUH TEGANGAN DAN KUAT ARUS LISTRIK TERHADAP SIFAT MEKANIS MATERIAL PADA LAPISAN MATERIAL COOPER AW 14 GA + 13Cr STAINLESS HASIL DARI TEKNIK ARC SPRAYED - Prastowo, Sahid; Sugeng, Margono (Bina Teknika, 2015)
Many things can affect the quality of Arc Sprayed process, including the process of setting the parameters of the machine, especially large current and voltage settings on the machine Arc Sprayed burning electricity (in this study using the machine SULZER METCO TUBE models 300). Given it is done research on comparative analysis of the microstructure of the material hardness and cooper wire AW 14 GA and 13Cr steel which will be used as the standard parameters on PT. X by using some variation of voltage (voltage) and current (ampere) on the machine SULZER METCO TUBE 300 models that aim to make the coating material sprayed results arc process. Coating or coating aims to improve the mechanical properties of the material or industrial goods that are far superior and quality of existing or recondition the mechanical properties of the material originally kekondisi. One example of that is the Arc Sprayed coatings using Copper material AW 14GA and 13Cr steel. The amount of electric current used in this study for 200A, 225A, 250A, and 275A and a large voltage that is used for 26V, 28V, 30V and 32V with standard minimum hardness of 118 HV and 372 HV hardness maximum amount and there is no porosity of testing photo material micro structure. From the research, it was found that the magnitude of the ideal machine parameters in accordance with the quality standards that have been set, namely the+32V 250A engine parameters, and the parameters used as the standard parameters for the production process in PT. X.